2018
DOI: 10.1002/lary.27397
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐Enhanced Ultrasound With Perflubutane for Sentinel Lymph Node Mapping in Cutaneous Melanoma: A Pilot Study

Abstract: Objective To study the feasibility of contrast‐enhanced ultrasound (CEUS) for identification of SLN associated with cutaneous melanoma. Study Design Single arm pilot study in a swine animal model. Methods One milliliter of perflubutane (Sonazoid, GE Healthcare, Milwaukee, WI) was injected into the peritumoral dermis in five swine with cutaneous melanoma. Ultrasonography was used to follow enhancing lymphatic channels to lymph nodes (LN). Intradermal injection of vital blue (VB) dye was used as a positive contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…This technique offers a non-invasive liquid biopsy approach for metastatic cancer staging and treatment. PFC-labeled MBs can thus help biopsy sentinel lymph nodes in breast cancer, potentially replacing axillary surgery [478,479], and has entered routine practice in certain medical centers [480]. Targeted USpheres MBs were used for in vivo characterization of programmed death ligand-1 (PD-L1)-expressing cells in a mouse model [481].…”
Section: Delivery or Removal Of Therapeutic Gases Other Than Oxygenmentioning
confidence: 99%
“…This technique offers a non-invasive liquid biopsy approach for metastatic cancer staging and treatment. PFC-labeled MBs can thus help biopsy sentinel lymph nodes in breast cancer, potentially replacing axillary surgery [478,479], and has entered routine practice in certain medical centers [480]. Targeted USpheres MBs were used for in vivo characterization of programmed death ligand-1 (PD-L1)-expressing cells in a mouse model [481].…”
Section: Delivery or Removal Of Therapeutic Gases Other Than Oxygenmentioning
confidence: 99%
“…Nevertheless, the efficiency of CEUS for SLN characterization (benign versus malignant) is limited. Recently, Bertelsen et al, confirmed these results and suggested that CEUS may be useful for accurate SLN dissection (Figure 4) (Bertelsen, et al 2019). Moreover, Liu et al, reported that secondary LNs can also be detected with CEUS after direct injection of MBs into contrast-enhanced SLNs .…”
Section: Lymph Nodesmentioning
confidence: 81%
“…However, Bertelsen et al, identified three main limitations of this method (Bertelsen, et al 2019): 1) the radiotracer detects secondary LNs, resulting in their dissections, thereby increasing operative time and morbidity; 2) if the primary lesion is located near the draining nodal basins in areas with a dense lymphatic supply, the use of a hand-held gamma probe is more challenging; and 3) lymphoscintigraphy does not offer depth information for anatomic SLN localization. To overcome this issue, the surgeon removes LNs and assesses them ex-vivo using a gamma probe.…”
Section: Lymph Nodesmentioning
confidence: 99%
“…Perflubutane is a relatively new, second generation US contrast agent with some additional characteristics over the more commonly used sulfur hexafluoride (Sonovue®, Bracco, Milan, Italy) such as its affinity for reticuloendothelial cells [ 23 , 24 ]. Like sulfur hexafluoride, it is well tolerated and has no major contraindications or severe known adverse effects when administered by intravenous or subdermal injections [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%